Assessment of epidemic risk state and its change trend of public hospital in underdeveloped area in different stages - Yang, Ming; Miao, Jingjing; Li, Tiebing; Jiang, Rong; Jiang, Min (Frontiers in Public Health, 2024)
Objective Epidemics are sudden and rapidly spreading. Hospitals in underdeveloped areas are particularly vulnerable in case of an outbreak. This paper aims to assess the epidemic risk state and its change trend of hospitals in different epidemic stages, identify the key factors affecting hospital epidemic risk change, provide priority reference for hospital epidemic risk control, and enhance the hospital's ability to respond to sudden epidemics. Methods Based on Grounded theory, the epidemic risk indicators that affect hospital safety are summarized. The concept of epidemic risk state and its random state space is proposed according to Markov chain theory. The impact of each indicator on the random risk state and its change is comprehensively assessed from two aspects: risk occurrence probability and risk loss. Finally, the assessment of the hospital epidemic risk state and its change at different stages is achieved. Results The stable risk states of public hospitals in underdeveloped areas in non-epidemic stage t0, early epidemic stage t1, and outbreak stage t2 are P^t0(Sn)=0.142,0.546,0.220,0.093, P^t1(Sn)=0.025,0.364,0.254,0.357, and P^t2(Sn)=0.020,0.241,0.191,0.548, respectively. In non-epidemic stage, the key factor in improving the hospital epidemic risk state is emergency funding. In early epidemic stage, the key factors in improving the hospital epidemic risk state are the training of medical staff in epidemic prevention skills and the management of public health. In outbreak state, the key factor in improving the hospital epidemic risk state is the training of medical staff in epidemic prevention skills and psychological awareness. Conclusion This paper proposes the concept of epidemic risk state, providing an effective assessment method for the epidemic risk state and its change trend in public hospitals. According to the assessment, public hospitals in underdeveloped areas in different epidemic stages should adopt different risk control strategies to improve their current risk state. Blind risk control is inefficient and may even cause the epidemic risk to transition toward a more dangerous state.